Investigation of the drug «Cycloferon» influence on the morbidity of acute respiratory viral infections and flu and condition of local immunity in children of different age groups - Ye. I. Kondratieva; L. A. Matveeva; Ye. Yu. Tyuteva; N. A. Ryzhakova; A. A. Terentieva; Yu. I. Logvinenko (Бюллетень сибирской медицины, 2006)
The aim of the research was the investigation of prophylactic using the drug «Cycloferon». Influence of Cycloferon on acute respiratory viral infection and flu and on their clinical manifestations as well as on local immunity condition was assessed. We examined 124 children aged from 4 to 18 years. It was revealed that duration of acute respiratory viral infections as well as flu decreased and local immunity of the upper respiratory ways increased considerably in children taking Cycloferon. The abovementioned changes were observed both just after the treatment and in the follow-up period.